EFEKTIVITAS MEDIA PROMOSI PADA PRODUK SANDWICH GORENG MEREK ROYAL SANDWICH - Laila Afifah; Mudatsir Najamuddin; Bintan Humaeira (Departement of Agribusiness Faculty of Science and Technology, 2019)
Marketing is a significant point in agriculture. Without marketing, products that have been resulted may be difficult to sale. Marketing is not just a method to sell products as many as possible for benefits, but it is also the way to keep the existence of produced products on the market. The company also needs to communicate the product and the company itself to the customers, especially in the situation of fierce competition. One of the marketing successes is influenced by the promotions. Many products are not successful in the market because of the promotions failure although in terms of quality are well-established if compared with the other products (simamora, 2003: 284). Promotion program that currently favored by business is by using social media as a way to promote their products especially in companies with low budget. One of companies that uses social media to promote the products is Royal Sandwich. Royal Sandwich is one of the UKM (small and medium enterprises) in the field of convenience food. The aims of this study are: 1) Recognizing various promotion conducted by the Royal Sandwich. 2) Analyzing the effectiveness of promotion media of the fried sandwich product by Royal Sandwich based on the impact of communication. 3) Analyzing the effectiveness of promotion media of the fried sandwich product by Royal Sandwich based on the impact of sale.